Induced innovation and relavtive factor share - Lu, Yanpin (2011)
We build up an induced innovation model based on Popp's article in AER, 2002. His model measured the effect of energy prices on energy-efficient innovations. Using the relative factor shares of energy and labor instead of the energy prices per se, we are able to explain the patenting activity in a better way. Also, with the combination of theoretical and empirical research, we can prove that technological change of energy is related with prices and quantities of both energy factor and labor factor. Furthermore, we discuss on the possibility of the hypothesis of diminishing returns to knowledge, which reveals that diminishing returns are not necessary to exist in the induced innovation model. The result we got is not very strong but it shows more elasticity than Popp’s model.